High expression of human carboxypeptidase M in Pichia pastoris: Purification and partial characterization - R.B. Craveiro; J.D. Ramalho; J.R. Chagas; P.H.M. Wang; D.E. Casarini; J.L. Pesquero; R.C. Araújo; J.B. Pesquero (Brazilian Journal of Medical and Biological Research, 2006)
Carboxypeptidase M (CPM) is an extracellular glycosylphosphatidyl-inositol-anchored membrane glycoprotein, which removes the C-terminal basic residues, lysine and arginine, from peptides and proteins at neutral pH. CPM plays an important role in the control of peptide hormones and growth factor activity on the cell surface. The present study was carried out to clone and express human CPM in the yeast Pichia pastoris in order to evaluate the importance of this enzyme in physiological and pathological processes. The cDNA for the enzyme was amplified from total placental RNA by RT-PCR and cloned in the vector pPIC9, which uses the methanol oxidase promoter and drives the expression of high levels of heterologous proteins in P. pastoris. The cpm gene, after cloning and transfection, was integrated into the yeast genome, which produced the active protein. The recombinant protein was secreted into the medium and the enzymatic activity was measured using the fluorescent substrate dansyl-Ala-Arg. The enzyme was purified by a two-step protocol including gel filtration and ion-exchange chromatography, resulting in a 1753-fold purified active protein (16474 RFU mg protein-1 min-1). This purification protocol permitted us to obtain 410 mg of the purified protein per liter of fermentation medium. SDS-PAGE showed that recombinant CPM migrated as a single band with a molecular mass similar to that of native placental enzyme (62 kDa), suggesting that the expression of a glycosylated protein had occurred. These results demonstrate for the first time the establishment of a method using P. pastoris to express human CPM necessary to the development of specific antibodies and antagonists, and the analysis of the involvement of this peptidase in different physiological and pathological processes